Sosialisasi Dan Rancangan Jaringan Pipa Air Bersih Di Desa Kampung Pinang Kecamatan Perhentian Raja Kabupaten Kampar - roza mildawati; Yolly Adriati; Rizdqi Akbar Ramadhan; Riskon Ramadhan; Dhany Fauzan Azhimy (Universitas Lancang Kuning, 2023)
The need for clean water in Indonesia is still not distributed evenly. Clean water is not distributed evenly due to obstacles and problems. Based on observations in Kampung Pinang Village, Kampar Regency, there is already a clean water reservoir, but in the reservoir there is no clean water distribution system available to homes to meet community needs. To analyze the problems and efforts to complete this research, the researcher uses a literature study that is used to obtain clarity of concepts in research, namely by obtaining books, journals, and previous research, which contains the basics of theory and calculation formulas, and obtains data that support in completing this research, namely secondary data in the form of population data, village maps and other data obtained directly from parties related to this research. The planning of a clean water system network using EPANET 2.0 software in hamlet 1, Kampung Pianang village, Kampar Regency is carried out using the gravity method and using a pump where the water source comes from an existing reservoir. The projected population of Kampung Pinang until 2030 is 1385 people, so by analyzing water needs, it is found that the need for clean water in 2030 is 1.742 l/second. From the simulation results of the EPANET 2.0 software using the gravity method on the clean water network in the village of Kampung Pinang, the highest pressure value is 11.97 m at junction J4 and the lowest pressure is 3.80 m at junction J20. Meanwhile, all pressure values using a pump have met the requirements. The highest velocity (velocity) is 0.14 m/s on pipe P1 and pipe P2 and the lowest speed is 0.01 m/s on pipe P12. The highest energy loss (headloss) is 0.39 m/km in the P1 and P2 pipes and the lowest energy loss is 0.01 m/km in the P12 pipes.